Dietary effect of probiotics and prebiotics on broiler performance, carcass, and immunity - Rehman, A.; Arif, M.; Sajjad, N.; Al-Ghadi, M.Q.; Alagawany, M.; Abd El-Hack, M.E.; Alhimaidi, A.R.; Elnesr, S.S.; Almutairi, B.O.; Amran, R.A.; Hussein, E.O.S.; Swelum, A.A. (Poultry science, 2020)
This experiment was carried out to evaluate the effects of dietary addition of probiotics (Protexin) and prebiotics (active MOS, mannan oligosaccharides) on growth performance, carcasses, and antibody titer in broilers. A total number of 360-day-old Ross broiler chicks were randomly divided into 9 groups in a 3 × 3 factorial arrangement. Nine broiler starter (0–21 d) and finisher (21–35 d) diets were formulated by using 3 levels of probiotics (0, 1, and 2 g/kg of feed) and 3 levels of MOS (0, 1, and 1.5 g/kg of feed) and were randomly allotted to 9 groups. Feed intake was not affected by interaction of treatments during all phases (P > 0.05). Feed intake was improved due to the main effect of probiotic (P = 0.0001) or MOS (P = 0.005). No interaction (P > 0.05) was observed for weight gain in the starter, finisher, and overall phases. While, during the starter and finisher phases, weight gain was increased by probiotics (P = 0.028 or 0.04, respectively). Dietary supplementation of MOS improved weight gain (P = 0.01) and feed conversion ratio (FCR) (P = 0.03) during the overall period, but during starter and finisher periods, weight gain and FCR were not affected by prebiotics. Apart from dressing percentage, no interaction or individual effect of probiotics and prebiotics was observed for carcass, breast, thigh, heart, liver, and gizzard weight. Antibody titer for infectious bursal disease (IBD) was improved (P = 0.026) by the interaction effect between probiotics and prebiotics, when compared with the control group. Antibody titer against Newcastle disease (ND) was not affected by probiotics or prebiotics or their interactions (P > 0.05). It could be concluded that supplementation of prebiotics or probiotics can improve the growth performance of broilers. It may also be helpful in improving the antibody titer against IBD in broilers fed antibiotic-free diets.